Optimization of biologics to reduce treatment failure in inflammatory bowel diseases. (October 2020) - Bourchany, Aurélie; Gilletta De Saint-Joseph, Cyrielle; Breton, Anne; Barreau, Frédérick; Mas, Emmanuel
Highlights: Therapeutic drug monitoring should be used to optimize anti-TNFα drugs. Predictive factors may be useful to personalize drug use. Few data are available for non anti-TNFα biologics. Drug development targeting intestinal epithelium dysfunction, for example, microbiota and intestinal barrier impairment, are mandatory. Abstract : Moderate to severe inflammatory bowel disease patients can fail to respond to conventional therapy and/or to biologic treatment. In the era of TNFα antagonists and other non-anti-TNF biologic drugs, it is important to review the literature on biologic treatment failure, which could be defined as primary non-response, secondary loss of response and intolerance. Therapeutic drug monitoring (TDM), that is, drug trough level and antidrug antibodies, should enable to determine the mechanisms of treatment failure and to optimize drug efficacy. There is a consensus on reactive TDM at the time of loss of response. Proactive TDM could be of interest during induction and/or maintenance, but randomized controlled trials are required.